Development and Implementation of Smart Eco-STEAM Technology to Reduce Defects and Improve Efficiency in Ecoprint MSMEs - Kholifah, Nur; Puspito, Jarwo; Sunarta, Sunarta; Nurtanto, Muhammad; Nancy Elizabeth, Goda (Universitas Ahmad Dahlan, 2025)
Background: Ecoprint micro, small, and medium-sized enterprises (MSMEs) face persistent challenges, including production inefficiencies, high defect rates, and limited market adaptability due to reliance on manual processes. This study aims to develop and implement a holistic framework that enhances sustainability and competitiveness through technological innovation, skill enhancement, and stakeholder collaboration. Contribution: The study contributes to a replicable innovation model that empowers artisans, strengthens ecological sustainability, and improves operational efficiency. Method: Using a Participatory Action Research (PAR) approach, 12 purposively selected ecoprint artisans from Tembindigo MSME in Yogyakarta participated in the co-design and testing of Smart Eco-STEAM technology. Data was collected through observation, interviews, questionnaires, and production records, and analyzed using descriptive and comparative statistics. Results: The implementation of Smart Eco-STEAM reduced defective products from 35% to 12%, achieved energy savings of 37%, and shortened steaming time by 45 minutes per cycle, enabling a twofold increase in daily output. Artisans reported greater ease of use, improved motif quality, and increased confidence in handling larger orders. Conclusion: The findings confirm that Smart Eco-STEAM effectively addresses key production barriers while aligning ecological sustainability with operational efficiency.